Confirmed Activity and Tolerability of Weekly Paclitaxel in the Treatment of Advanced Angiosarcoma. (25th February 2016) - Apice, Gaetano; Pizzolorusso, Antonio; Di Maio, Massimo; Grignani, Giovanni; Gebbia, Vittorio; Buonadonna, Angela; De Chiara, Annarosaria; Fazioli, Flavio; De Palma, Giampaolo; Galizia, Danilo; Arcara, Carlo; Mozzillo, Nicola; et al.
Abstract : Background. In several prospective and retrospective studies, weekly paclitaxel showed promising activity in patients with angiosarcoma. Patients and Methods . Our study was originally designed as a prospective, phase II multicenter trial for patients younger than 75, with ECOG performance status 0–2, affected by locally advanced or metastatic angiosarcoma. Patients received paclitaxel 80 mg/m 2 intravenously, at days 1, 8, and 15 every 4 weeks, until disease progression or unacceptable toxicity. Primary endpoint was objective response. Results . Eight patients were enrolled but, due to very slow accrual, the trial was prematurely stopped and further 10 patients were retrospectively included in the analysis. Out of 17 evaluable patients, 6 patients obtained an objective response (5 partial, 1 complete), with an objective response rate of 35% (95% confidence interval 17%–59%). Of note, five responses were obtained in pretreated patients. In the paper, details of overall survival, progression-free survival, and tolerability are reported. Conclusions . In this small series of patients with locally advanced or metastatic angiosarcoma, weekly paclitaxel was confirmed to be well tolerated and active even in pretreated patients.